Prediction of gestational diabetes mellitus in the Born in Guangzhou Cohort Study, China. Issue 2 (6th August 2018) - Schaefer, Kimberly K.; Xiao, Wanqing; Chen, Qiaozhu; He, Jianrong; Lu, Jinhua; Chan, Fanfan; Chen, Niannian; Yuan, Mingyang; Xia, Huimin; Lam, Kin Bong Hubert; Hirst, Jane E.; Qiu, Xiu
Abstract: Objective: To assess potential risk factors in identifying women at risk for gestational diabetes mellitus (GDM). Methods: The present study included data collected as part of a prospective cohort study, and included women with singleton pregnancies who underwent initial prenatal examination at a tertiary women and children's hospital in Guangzhou, China between February 1, 2012, and December 31, 2015. Maternal characteristics and medical history were investigated to evaluate associations with GDM. A risk factor scoring system for the prediction of GDM was generated using logistic regression. Results: Overall, 1129 (13.5%) of 8381 women were diagnosed with GDM. Women older than 35 years had a 3.95‐fold increased risk of GDM (95% confidence interval 2.80–5.58) compared with women aged 16–25 years; obese women had a 6.54‐fold higher risk (95% confidence interval 3.50–12.23) compared with underweight women. A risk scoring system was established based on age, body mass index, family history of diabetes, weight gain, and history of GDM. Screening for women with a score of 12 or more would have reduced the number undergoing oral glucose tolerance testing by 2131 (25.4%) patients with a sensitivity of 87% for GDM detection. Conclusion: The assessment of risk factors for GDM could provide a foundation for improving risk‐based screening strategies in this and similar populations. Abstract : Use of a risk‐factor‐based screening tool for gestational diabetes mellitus could reduce the number of pregnant women undergoing oral glucose tolerance testing by 25%.